The Centenary of Immune Thrombocytopenia – Part 1: Revising Nomenclature and Pathogenesis - Consolini, Rita; Legitimo, Annalisa; Caparello, Maria Costanza (Frontiers in Pediatrics, 2016)
The natural history of the Immune Thrombocytopenia (ITP) is interesting and intriguing because it traces different steps underlying autoimmune diseases. The review points out the main steps that have accompanied the stages of its history and the consequential changes related to its terminology. ITP is an autoimmune disease resulting from platelet antibody- mediated destruction and impaired megakaryocyte (MK) and platelet production. However, research advances highlight that a complex dysregulation of the immune system is involved in the pathogenesis of this condition. The review examines the role of the multiple immune components involved in the autoimmunity process, focusing on the more recent mechanisms which could be new promising therapeutic targets for ITP patients.